The Effects of Maintenance Strategy on Equipment Performance in Heavy Industry Operations in South Africa - Bhengu, Bongani (University of the Witswatersrand, Johannesburg, 2023)
Existing literature in maintenance strategy selection does not quantify the relative benefit of each applied maintenance strategy, neither does it indicate the perceived benefit to maintenance practitioners. The existing literature does not enable inference to be made to the South African context of Pulp, Paper and Packaging Sector. Therefore, for South African maintenance practitioners, who want to know which strategy within South Africa (SA), is associated with a consequential world class equipment performance, there is no literature that provides adequate quantitative information. Therefore, this research article seeks to close the abovementioned research gap. Two research questions needed to be investigated quantitatively, the first question is “what maintenance strategy in the target industry achieves competitive equipment availability?”, the research results showed that PdM strategies are perceived to be the strategies that achieve the most competitive availability. The second research question is “What strategy is widely used in SA’s Heavy Industries, particularly Pulp, Paper and Packaging sector?”. The finding on this research question, is that combined, or hybrid strategies are applied by 67.9% of the sample, 21.4% applies PM strategies, 7.1% PdM strategies. This finding should trigger managerial practical questions, such as “why a such small portion of PdM strategies are in practice?”, if they are perceived to provide consequently competitive equipment performance. The third part of this research, focused on deriving and testing a mathematical model of availability as a function of maintenance strategy applied. The model derived was found to be reasonably reliable, and valid, as the independent variables utilized explained 84.3% of the model, which is acceptable. vi The key findings, and success of this research article, is that a mathematical model that was postulated, explains the consequential equipment performance as a function of maintenance strategy applied. Therefore, inference could be cautiously made, that this model possessed a reasonable degree of internal and external validity and could therefore be employed by the target population to fine tune and achieve the desired equipment availability
The Effects of Maintenance Strategy on Equipment Performance in Heavy Industry Operations in South Africa
Keywords: Maintenance Management; Maintenance Strategy; UCTD; Equipment Performance; Heavy Industry Operations; South Africa; SDG-8: Decent work and economic growth